Hepatic ChREBP orchestrates intrahepatic carbohydrate metabolism to limit hepatic glucose 6-phosphate and glycogen accumulation in a mouse model for acute Glycogen Storage Disease type Ib - K.A. Krishnamurthy; M.G.S. Rutten; J.A. Hoogerland; T.H. van Dijk; T. Bos; M. Koehorst; M.P. de Vries; N.J. Kloosterhuis; H. Havinga; B.V. Schomakers; M. van Weeghel; J.C. Wolters; et al. (Elsevier, 2024)
Objective: Carbohydrate Response Element Binding Protein (ChREBP) is a glucose 6-phosphate (G6P)-sensitive transcription factor that acts as a metabolic switch to maintain intracellular glucose and phosphate homeostasis. Hepatic ChREBP is well-known for its regulatory role in glycolysis, the pentose phosphate pathway, and de novo lipogenesis. The physiological role of ChREBP in hepatic glycogen metabolism and blood glucose regulation has not been assessed in detail, and ChREBP's contribution to carbohydrate flux adaptations in hepatic Glycogen Storage Disease type 1 (GSD I) requires further investigation. Methods: The current study aimed to investigate the role of ChREBP as a regulator of glycogen metabolism in response to hepatic G6P accumulation, using a model for acute hepatic GSD type Ib. The immediate biochemical and regulatory responses to hepatic G6P accumulation were evaluated upon G6P transporter inhibition by the chlorogenic acid S4048 in mice that were either treated with a short hairpin RNA (shRNA) directed against ChREBP (shChREBP) or a scrambled shRNA (shSCR). Complementary stable isotope experiments were performed to quantify hepatic carbohydrate fluxes in vivo. Results: ShChREBP treatment normalized the S4048-mediated induction of hepatic ChREBP target genes to levels observed in vehicle- and shSCR-treated controls. In parallel, hepatic shChREBP treatment in S4048-infused mice resulted in a more pronounced accumulation of hepatic glycogen and further reduction of blood glucose levels compared to shSCR treatment. Hepatic ChREBP knockdown modestly increased glucokinase (GCK) flux in S4048-treated mice while it enhanced UDP-glucose turnover as well as glycogen synthase and phosphorylase fluxes. Hepatic GCK mRNA and protein levels were induced by shChREBP treatment in both vehicle- and S4048-treated mice, while glycogen synthase 2 (GYS2) and glycogen phosphorylase (PYGL) mRNA and protein levels were reduced. Finally, knockdown of hepatic ChREBP expression reduced starch domain binding protein 1 (STBD1) mRNA and protein levels while it inhibited acid alpha-glucosidase (GAA) activity, suggesting reduced capacity for lysosomal glycogen breakdown. Conclusions: Our data show that ChREBP activation controls hepatic glycogen and blood glucose levels in acute hepatic GSD Ib through concomitant regulation of glucose phosphorylation, glycogenesis, and glycogenolysis. ChREBP-mediated control of GCK enzyme levels aligns with corresponding adaptations in GCK flux. In contrast, ChREBP activation in response to acute hepatic GSD Ib exerts opposite effects on GYS2/PYGL enzyme levels and their corresponding fluxes, indicating that GYS2/PYGL expression levels are not limiting to their respective fluxes under these conditions.